2022
DOI: 10.1177/23259582221107327
|View full text |Cite
|
Sign up to set email alerts
|

“We Feel Like Everybody's Going to Judge us”: Black Adolescent Girls’ and Young Women's Perspectives on Barriers to and Opportunities for Improving Sexual Health Care, Including PrEP, in the Southern U.S

Abstract: Black adolescent girls and young women (AGYW) are disproportionately affected by HIV in the southern U.S.; however, PrEP prescriptions to Black AGYW remain scarce. We conducted in-depth interviews (IDIs) with Black AGYW ages 14-24 in Alabama to explore opportunities for and barriers to sexual health care including PrEP prescription. Twelve AGYW participated in IDIs with median age 20 (range 19-24). All reported condomless sex, 1-3 sexual partners in the past 3 months, and 6 reported prior STI. Themes included:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…The 5 domains are (1) intervention characteristics or innovation (ie, the product or the “thing” being implemented), (2) inner setting (ie, setting where the innovation is being carried out), (3) outer setting (ie, setting where the inner setting exists), (4) individuals (ie, roles and responsibilities of individuals), and (5) implementation process (ie, various activities carried out to implement the innovation) [ 44 ]. For example, the individual-level determinants at the provider level that may influence PrEP prescription include knowledge and beliefs around PrEP and conducting a sexual history or risk assessment, and self-efficacy as identified in our studies and also supported by prior literature [ 21 , 22 , 24 , 31 , 45 ]. The inner setting determinants include readiness for change, ease of access to knowledge and information about sexual history taking and PrEP, and leadership engagement within FM training programs to innovate and provide research opportunities for residents.…”
Section: Methodssupporting
confidence: 75%
See 1 more Smart Citation
“…The 5 domains are (1) intervention characteristics or innovation (ie, the product or the “thing” being implemented), (2) inner setting (ie, setting where the innovation is being carried out), (3) outer setting (ie, setting where the inner setting exists), (4) individuals (ie, roles and responsibilities of individuals), and (5) implementation process (ie, various activities carried out to implement the innovation) [ 44 ]. For example, the individual-level determinants at the provider level that may influence PrEP prescription include knowledge and beliefs around PrEP and conducting a sexual history or risk assessment, and self-efficacy as identified in our studies and also supported by prior literature [ 21 , 22 , 24 , 31 , 45 ]. The inner setting determinants include readiness for change, ease of access to knowledge and information about sexual history taking and PrEP, and leadership engagement within FM training programs to innovate and provide research opportunities for residents.…”
Section: Methodssupporting
confidence: 75%
“…Multilevel barriers to PrEP provision and uptake include client-level barriers (such as low PrEP awareness, mistrust of the health care system, and PrEP-associated stigma) [18][19][20][21], health care system-level barriers (such as knowledge gaps and comfort among providers, unconscious bias, and racism) [22][23][24], and structural-level barriers (such as costs, reimbursement, and lack of health insurance) [24][25][26]. More specifically, in the South, PrEP provision and uptake have been limited by geographical factors-living in rural areas with limited access to PrEP providers [7], provider and health care system factors, including PrEP knowledge [27], provider sexual assessment skills [27], perceived provider racism [28], PrEP stigma [28,29], and health care capacity, among many other factors [7,30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PrEP-related stigma was evidenced in families, schools, and in healthcare settings among HCPs otherwise charged with supporting health and prevention, and intersected with sexual-, gender nonconformity-, and HIVstigma, similar to intersectional PrEP stigma described among racialized youth in the United States. 36 PrEP stigma was also evidenced in adolescents' intimate relationships, with PrEP signifying mistrust; while not unique to MSM partners in Thailand, 40,41 PrEP stigma may be animated by values that privilege relational harmony over individual needs. 32 In addition to elucidating the network of factors that constrain adolescents' engagement with PrEP, our multilevel practice-based analysis suggests directions for programmatic initiatives, policy advocacy, and research to strategically position PrEP as a viable prevention tool for gay and transgender adolescents in Thailand.…”
Section: Discussionmentioning
confidence: 99%
“…What remains predictable are multilevel symbolic representations of PrEP, more so among adolescents. Thailand is not socially or culturally unique in the stigma surrounding PrEP use 36 , 37 ; however, internalized and enacted stigma among MSM and TGW in Thailand 27 , 38 may be amplified in a system that is imbued with powerful norms about propriety (eg, how, when, and with whom adolescents can talk about sex and HIV among adults) and deferring one's private individual needs to maintain public social harmony (with parents, teachers, HCPs). 39 PrEP becomes emblematic of social and cultural impropriety: if adolescents shouldn’t talk with adults about sex or be known to engage in sex, PrEP access requires defiance of sociocultural norms—the antithesis of an enabling environment.…”
Section: Discussionmentioning
confidence: 99%
“…Black women in our study voiced needing more information on mental health, reproductive health and family planning, and conditions related to weight management and obesity. This finding is crucial, as studies have found that while mHealth apps can optimize and promote health, they tend to be frequently underused after they are downloaded [27,28]. One study reported that the critical drivers of abandonment of mHealth apps include loss of interest, thus indicating the importance of ensuring that apps are developed in a manner that prioritizes the health needs of users [29].…”
Section: Principal Findingsmentioning
confidence: 99%